2015
DOI: 10.1097/md.0000000000002087
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk After Bariatric Surgery

Abstract: Bariatric surgery has been shown to impair bone health. This study aimed to investigate the fracture risk in patients after bariatric surgery versus propensity score-matched controls. The authors used the National Health Insurance Research Database of Taiwan and identified 2064 patients who underwent bariatric surgery during 2001 to 2009. These patients were matched to 5027 obese patients who did not receive bariatric surgery, using propensity score matching accounting for age, sex, Charlson Comorbidity Index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(36 citation statements)
references
References 37 publications
(44 reference statements)
3
33
0
Order By: Relevance
“…Four studies (Ikramuddin et al , 2015; Lalmohamed et al , 2012; Lu et al , 2015; Maghrabi et al , 2015) were included that assessed incident self‐reported fractures (any site) with the fracture outcome were measured by incident per patient year . Our data indicated a trend towards an increased fracture risk in the surgical population ( n = 6,811) compared to controls ( n = 25,285) (RR = 1.24; 95% CI: 0.99, 1.56; p = 0.06; I 2 = 0%) (Table , Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…Four studies (Ikramuddin et al , 2015; Lalmohamed et al , 2012; Lu et al , 2015; Maghrabi et al , 2015) were included that assessed incident self‐reported fractures (any site) with the fracture outcome were measured by incident per patient year . Our data indicated a trend towards an increased fracture risk in the surgical population ( n = 6,811) compared to controls ( n = 25,285) (RR = 1.24; 95% CI: 0.99, 1.56; p = 0.06; I 2 = 0%) (Table , Figure ).…”
Section: Resultsmentioning
confidence: 75%
“…Moreover, bone loss at both peripheral and central skeletal locations persists beyond the period of weight loss implying that additional mechanisms may be responsible for bone loss following bariatric surgery that include nutritional deficiencies, and alterations in adipokines and gut-derived appetite-regulatory hormones [92]. Interestingly, the clinical impact of skeletal change following bariatric surgery manifests later with an increase in fracture risk observed 3-years post-operatively [9698]. Vitamin D deficiency, hyperparathyroidism and calcium malabsorption following malabsorptive procedures such as RYGB is of concern [99] particularly in a background of vitamin D deficiency in obese patients pre-operatively [100].…”
Section: The Impact Of Bariatric Surgery On Bone Health In Adolescentsmentioning
confidence: 99%
“…Although RYGB and SG are highly effective for reduction of weight and metabolic comorbidities, their effects on the skeleton appear harmful. Studies have shown detrimental effects of bariatric surgery on bone and mineral metabolism (24) and an increase in fracture risk (5, 6). …”
Section: Introductionmentioning
confidence: 99%